EPIDEMIOLOGY AND SEASONAL VARIATION OF APPENDICITIS – A SINGLE CENTER RETROSPECTIVE STUDY FROM NORTH-EAST INDIA - Kumar, R.; Singh, T. B.; Pandey, R.; Bhalla, S.; Singh, O. (International Journal of Medicine and Medical Research, 2022)
Background. Acute appendicitis is the most common surgical emergency presenting in emergency department, and appendectomy is one of the most common surgeries. There is a wide variation in the incidence of acute appendicitis reported for different countries, different regions, race, sex, age and also seasons. Objective. The aim of this study was to understand the epidemiological trend and the seasonal variation of appendicitis in the northeast region of India. Methods. It was a retrospective hospital-based study conducted in Jan 2016 – Dec 2020 at a Tertiary Care Teaching Hospital in the northeast region of India. The patient data were obtained from the Medical Record Department of the hospital and the data regarding the weather was obtained from the Indian Meteorological Department (IMD) and the website www.worldweather.com. The statistical analysis was done using SPSS software version 24.0, and the seasonal variation was studied using Kruskal Wallis test. Results. Acute appendicitis affected both the sexes equally with a marginal higher incidence in males. It also had higher peak during the second and third decade of life in both the sexes. The incidence of acute appendicitis was high in the pre-monsoon and monsoon season with peak in the monsoon season. Conclusions. Acute appendicitis is more common during the pre-monsoon and monsoon season, a period known for humidity, high incidence of bacterial and viral infections.